Songs that Carry Transformation: Pentecostal Praise and Worship Rituals in Nairobi, Kenya - Prosén, Martina (Mission studies, 2018)
In this article, the theological meaning of transformation is examined from the vantage point of a local Pentecostal church in Nairobi, Kenya, and its liturgical practices. The church under study is the Woodley branch of Christ is the Answer Ministries (CITAM Woodley), formerly Nairobi Pentecostal Church (NPC) Woodley, and data was collected through field research. Arguing with the help of Steven Land’s standard work Pentecostal Spirituality. A Passion for the Kingdom, it is demonstrated that praise and worship rituals function as vehicles for transformation in the theology/spirituality of the informants. Singing and making music are not optional or random activities, but constitute a core ritual providing congregants a viable route to a central goal of Pentecostal spirituality: transformation. Transformation is thus both an idea and a goal, and praise and worship rituals – including the songs sung in worship – constitute a crucial link between the two.